Climate Change Impact in the Tribal Localities of High Rainfall Zone of Tamil Nadu - Arunachalam , R (Indian Journal of Extension Education, 2023)
The study was conducted in the high rainfall zone of Tamil Nadu during the years 2022- 23 to document the impact of climate change, assess awareness and perception of the tribal communities and to suggest suitable strategies. The study was conducted in two tribal dominant villages of Kanyakumari district with 60 tribal respondents selected using simple random sampling technique. The PRA methods such as focused group discussion, seasonal calendar, time line and interactive group meetings were employed to document the climate based issues and further categorized in to eco system based, livelihood based and socio cultural life based. On these impacts, awareness and perception of the respondents were assessed. Standardized interview schedule was employed for data collection. The results showed a marginal increase in the maximum temperature and minimum temperature. Marginal declining trend was observed in relative humidity and rainfall distribution compared with the base year value. The wind behaviour showed an erratic variation. Respondents faced different issues on their livelihood, ecosystem and socio-cultural life. It has been suggested to establish a separate climate based nodal agency to address the issues of climate change in the tribal localities.
Keywords: Climate change; Impact; Ecosystem; Environment conservation; Awareness; Perception; Tribes